The Impact of Macroeconomics on Advancing MSME Development in Indonesia - Sunaryono, Sunaryono (East Asian Journal of Multidisciplinary Research, 2024)
Micro, Small and Medium Enterprises (MSMEs) contribute around 60% to Indonesia's Gross Domestic Product (GDP), playing a crucial role in economic development. MSME growth is the main focus, influenced by macroeconomic factors such as the BI Rate, inflation and exchange rate. This study uses secondary data from Bank Indonesia, BPS, and the Ministry of Cooperatives and Small and Medium Enterprises from 1997 to 2022. The quantitative analysis method using Eviews 10 shows that the BI Rate has a positive impact on the number of MSMEs but inflation and exchange rates have not. The conclusion of this study emphasizes the importance of appropriate policies to support the growth of the MSME sector and the economy as a whole.